2018
DOI: 10.3390/su10010232
|View full text |Cite
|
Sign up to set email alerts
|

Affective Policy Performance Evaluation Model: A Case of an International Trade Policy Implementation

Abstract: Firms often superficially adopt policies because of governmental rules and regulations, so as to avoid penalties or to gain benefits. However, the evaluation and characterization of those kinds of adoptions as policy performance distorts the true level of policy performance: social sustainability. This study proposes an affective policy performance evaluation model. The attitudes of employees toward adopting a policy are characterized into genuine and superficial compliance. Their behaviors are explained throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…We use the policy implementation analytical framework because it allows us to analyse RSPO's FPIC policy from different levels: Commitment, practice, and performance. Distinguishing different levels of analysis is useful to identify the problems and avoid a vague assessment of the RSPO's policy, and confusion between the formal adoption of a policy and its actual implementation (Kang et al, 2018, pp. 3–4).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We use the policy implementation analytical framework because it allows us to analyse RSPO's FPIC policy from different levels: Commitment, practice, and performance. Distinguishing different levels of analysis is useful to identify the problems and avoid a vague assessment of the RSPO's policy, and confusion between the formal adoption of a policy and its actual implementation (Kang et al, 2018, pp. 3–4).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Yu, W. et al focus on the effects of cross-border e-commerce from the perspective of the economics of transaction costs on the distance of trade and consumer welfare, analyzed information costs, negotiation costs, transportation costs, tariffs and costs, and showed that reducing transaction costs through policy intervention and contributing to the growth of international trade [18]. Kang, I. et al proposed a model for evaluating affective policy performance, analyzed structural equation measurement data through structural equation modeling methodology, and revealed that policy implementation by firms is the most effective resource to encourage firms' international trade policy adoption [19]. Ji, X. et al used the gregoro -hansen fusion method and vector error correction model in vector auto-correction model to reveal how international trade contributes to the sustainability of the economy, showing that exporting contributes to GDP growth and accelerates the improvement of import capacity in the long run [20].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [19] combined entropy weighting and the GRA to evaluate the CSR of eight airlines in China. Focusing on 216 trade policies, Kang et al [20] employed structural equation modeling to develop a trade strategy control system to identify attitudes toward using trade policies. The results encourage companies to adopt trade policies, and provide a practical model for resource allocation and policy administration.…”
mentioning
confidence: 99%